Efektivitas Kombinasi Limbah Ampas Teh (Camellia sinensis) Dan Limbah Kulit Bawang Putih (Allium sativum) Dalam Pembuatan Pupuk Organik Cair (POC) Terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens) - Indah Sari Rajab,; Siti Hardianti Ashari,; Multazam Kiswan Bachruddin, (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
This study aims to examine the effectiveness of combining tea waste (Camellia sinensis) and garlic peel waste (Allium sativum) in producing liquid organic fertilizer (LOF) on the growth of cayenne pepper plants (Capsicum frutescens). The research used a quantitative experimental method with four treatments over 15 days: no fertilizer, tea waste LOF, garlic peel LOF, and a combination of both. The results showed that garlic peel LOF produced the highest plant growth, reaching 39 mm on the 15th day. The combination of tea waste and garlic peel resulted in 27 mm growth, while tea waste LOF alone produced 14 mm. Plants without fertilizer grew only 1 mm. These findings indicate that garlic peel waste is more effective in promoting cayenne pepper growth compared to tea waste or their combination. The utilization of organic waste not only enhances plant productivity but also reflects Islamic values in preserving environmental sustainability.